1998
DOI: 10.1046/j.1365-2869.1998.00118.x
|View full text |Cite
|
Sign up to set email alerts
|

Insomnia in an 80‐year‐old population: Relationship to medical, psychological and social factors

Abstract: SUMMARYIn this study, insomnia in 80-year-olds was related to medical, psychological and social factors. The data were based on examinations every year in people aged between 80 and 89 years. Of 333 people living in the city of Lund and born in 1908, 67% participated. Increased severity of insomnia was significantly associated with use of diuretics, other cardiovascular drugs, hypnotics and laxatives, and with nervousness, difficulty relaxing, anorexia, nausea, constipation, backache, feeling cold, sweating, l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(31 citation statements)
references
References 2 publications
1
30
0
Order By: Relevance
“…Among older adults, insomnia severity was directly related to use of CV drugs, general fatigue, exhaustion, angina pectoris, cardiac insufficiency, worsened objective and subjective health, presence of negative T-waves on ECG and lower survival rates [11]. In another study, investigators observed that a combination of three sleep complaints (difficulty initiating sleep, difficulty maintaining sleep, and awakening tired and fatigued) predicted risk of CV disease [12].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among older adults, insomnia severity was directly related to use of CV drugs, general fatigue, exhaustion, angina pectoris, cardiac insufficiency, worsened objective and subjective health, presence of negative T-waves on ECG and lower survival rates [11]. In another study, investigators observed that a combination of three sleep complaints (difficulty initiating sleep, difficulty maintaining sleep, and awakening tired and fatigued) predicted risk of CV disease [12].…”
Section: Discussionmentioning
confidence: 99%
“…Evidence from several prospective studies suggests that insomnia may account for some of the risk not accounted for by anxiety in the association of anxiety with CV symptoms [10,11,12,13]. In addition, pathophysiological processes potentially important in generating CV events have been associated with insomnia [14].…”
Section: Introductionmentioning
confidence: 99%
“…Previously, studies have suggested that 'activity' is related to improvements in sleep quality. These activities range from exercise participation 14) (which suggest physiological mechanisms connecting exercise with increased sleep need) 15) to recreational 16) and social 17) activities. Our findings support the notion that social leisure activities, that are not necessarily associated with increased physical activity, are related to improvements in sleep quality.…”
Section: Discussionmentioning
confidence: 99%
“…A longitudinal study also found older adults, who felt subjectively lonely in the past, complained of more severe insomnia [13] . On the other hand, a crosssectional study found that a group of people with higher social interaction had shorter sleep latency [14] .…”
Section: Social Isolation and Sleep Disturbancementioning
confidence: 93%